Polityka mieszkaniowa w Polsce w latach 1990-2008. Budownictwo, zaludnienie, zarządzanie zasobami - Piechnik, Mieczysław (Housing Policy in Poland (1990-2008). Construction, Population, Resource Management, 2009)
Transformation of the socio-economic system initiated in 1989 included also the sector of a housing economy. Institutional and legal changes of the social sphere totally went away from so far accepted housing egalitarianism and formed at the beginning of the 90s the basis for the functioning of the housing market, targeted commercialization of, first of all, housing construction. A drastic restriction, since that moment, of public funds in solving housing situation of population being in a worse material situation. Therefore, over the years 1990-2008 there are significant slumps in housing construction. During this period, due to increased expenditure on housing purposes and household maintenance, the repair economy of housing resources, especially in communes, and rent arrears of the use of dwellings grew up because of economic reasons. Meeting housing needs in Poland on the European level requires an immediate increase of construction with a modern standard of dwellings equipment. For this purpose, it is necessary to mobilize additional economic-financial instruments in the housing policy of the country, in order to give new impetus to a more dynamic development of this economic sector. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 787-798